Lipids and Protein Peroxidation in Children and Teenager Patients with Pulmonary Tuberculosis - Yu.V. Poliakova (Zaslavsky O.Yu., 2015)
A review of literature about the study of lipid and protein peroxidation in children and teenagers with pulmonary tuberculosis nowadays was carried out. It was established that there is a great number works dedicated to the lipid peroxidation and antioxidant protective system in various pathological conditions of the respiratory system, including pulmonary tuberculosis in children and teenagers today. Oxidative modification proteins products are the earliest markers of oxidative stress in patients. There is no information on the oxidative modification of proteins in children and teenagers suffering from pulmonary tuberculosis in the literature. The study of oxidative modification of proteins will facilitate the development of more efficient new diagnosis methods and pathogenetic treatment of children and teenagers with pulmonary tuberculosis, that will increase the treatment effectiveness.